Optimal Sizing of Grid-Connected Wind-Solar-Biogas Integrated Energy System Considering Demand Response - YU Faqiang, ZHANG Mingjie, CHENG Yu, CHEN Dawei, YANG Hanyu, LI Canbing (Shanghai Jiaotong Daxue xuebao, 2023)
There are abundant biomass resources in China’s rural areas, which can be converted into biogas energy through fermentation systems. However, the rewards of the investments of the pure biogas projects is poor because biogas is a cheap resource. This paper proposes a 100% renewable grid-connected wind-solar-biogas integrated energy system which utilizes the complementarity between solar energy, wind energy, and biogas to provide users with biogas and electricity. The battery-like characteristics of biogas are modeled based on the microbial fermentation kinetic model and the temperature-sensitive characteristics of biogas fermentation. In addition, the demand-side response is considered to further increase the flexibility of the system, and the time-of-use electricity price is used to save power purchase costs, thereby minimizing investment costs and annual operating costs. Case studies show that the wind-solar-biogas micro-energy network can effectively reduce the total investment cost by 3% to 9% while increasing the benefit by 1.27 to 2.40 times.